Identification, Validation and Utilization of Novel Nematode-Responsive Root-Specific Promoters in Arabidopsis for Inducing Host-Delivered RNAi Mediated Root-Knot Nematode Resistance - Kakrana, Atul; Kumar, Anil; Satheesh, Viswanathan; Abdin, M. Z.; Subramaniam, Kuppuswamy; Bhattacharya, R. C.; Srinivasan, Ramamurthy; Sirohi, Anil; Jain, Pradeep K. (Frontiers in Plant Science, 2017)
The root-knot nematode (RKN), Meloidogyne incognita, is an obligate, sedentary endoparasite that infects a large number of crops and severely affects productivity. The commonly used nematode control strategies have their own limitations. Of late, RNA interference (RNAi) has become a popular approach for the development of nematode resistance in plants. Transgenic crops capable of expressing dsRNAs, specifically in roots for disrupting the parasitic process, offer an effective and efficient means of producing resistant crops. We identified nematode-responsive and root-specific (NRRS) promoters by using microarray data from the public domain and known conserved cis-elements. A set of 51 NRRS genes was identified which was narrowed down further on the basis of presence of cis-elements combined with minimal expression in the absence of nematode infection. The comparative analysis of promoters from the enriched NRRS set, along with earlier reported nematode-responsive genes, led to the identification of specific cis-elements. The promoters of two candidate genes were used to generate transgenic plants harboring promoter GUS constructs and tested in planta against nematodes. Both promoters showed preferential expression upon nematode infection, exclusively in the root in one and galls in the other. One of these NRRS promoters was used to drive the expression of splicing factor, a nematode-specific gene, for generating host-delivered RNAi-mediated nematode-resistant plants. Transgenic lines expressing dsRNA of splicing factor under the NRRS promoter exhibited upto a 32% reduction in number of galls compared to control plants.